Microplastic particles reduce EROD-induction specifically by highly lipophilic compounds in RTL-W1 cells - Heinrich, Patrick; Braunbeck, Thomas (Ecotoxicology and environmental safety, 2020)
Microplastic particles (MPs) from lipophilic polymers have been shown to efficiently accumulate hydrophobic organic contaminants (HOCs) in aquatic environments. MPs have, therefore, frequently been discussed as vectors for contaminants, enhancing HOC uptake by various organisms after ingestion followed by pollutant release; however, integrative models of sorption argue against this mechanism and even predict cleansing of pollutants from biological systems under particular circumstances. In order to experimentally investigate such a depuration mechanism, RTL-W1 cells were dosed with three 7-ethoxyresorufin-O-deethylase (EROD) inducers of distinct lipophilicity via the medium before adding both native and hexane-purified polyethylene MPs (20-25 μm) to the medium surface. EROD activity was significantly reduced in the presence of MP, the extent of which correlated with the inducers’ lipophilicity (KOW) and thus affinity to MP. For hexane-purged MPs and TCDD (KOW = 6.8), MPs reduce the bioavailability by up to 79%; the effect was marginally weaker with benzo[k]fluoranthene (KOW = 6.11) and almost absent with β-Naphthoflavone (KOW = 4.68). Compared to hexane-purged MPs, native particles possessed slightly less detoxification potential. These experimental results corroborate theoretically predicted mechanisms of detoxification via MPs. Yet, it is unclear if, under corresponding conditions in the environment, MPs can compete with organismal tissues for highly lipophilic compounds and, if so, to which degree they may act as a sink reducing the amount of bioavailable pollutants in situ. However, the present results suggest that in scenarios where pollutant-free MPs interact with organisms that accumulated HOCs via other routes of uptake, qualitatively the presence of such a mechanism is likely.
Available online 06 December 2019
Gesehen am 11.05.2020